Systematic review of methods and results of studies of the genetic epidemiology of ischemic stroke. - Flossmann, E; Schulz, U; Rothwell, P (2004)
BACKGROUND AND PURPOSE: To design appropriate molecular genetic studies, we first need to understand the genetic epidemiology of stroke. We therefore performed a systematic review of the literature to assess the heritability of stroke according to methodological quality of studies and to determine any heterogeneity in findings between studies and possible publication bias. METHODS: We searched for twin studies and studies of family history of stroke using bibliographic databases and by hand-searching reference lists and journals. Odds ratios (ORs) for family history as a risk factor for stroke were calculated within studies and combined by meta-analysis. Heterogeneity between studies, methodological quality of studies, and the influence of the age at which stroke occurred in both probands and relatives were assessed. RESULTS: We identified 53 independent studies (3 twin, 33 case-control, and 17 cohort). Monozygotic twins were more likely to be concordant than dizygotic twins (OR, 1.65; 95% CI, 1.2 to 2.3; P=0.003). A positive family history was a risk factor for stroke in both case-control (OR, 1.76; 95% CI, 1.7 to 1.9; P<0.00001) and cohort (OR, 1.30; 95% CI, 1.2 to 1.5; P<0.00001) studies. However, there was major heterogeneity between studies (cohort P=0.0001; case-control P<0.00001), with much stronger associations in small studies and methodologically less rigorous studies. Moreover, studies that reported insufficient data to allow meta-analysis tended to have found weaker associations. Family history of stroke was more frequent in studies that were confined to probands or relatives aged <70 years. However, few studies considered the number of affected and unaffected relatives, only 2 studies considered stroke phenotypes in detail, and only 19 studies (38%) adjusted associations for intermediate phenotypes. No twin study, only 5 cohort studies (26%), and 20 case-control studies (61%) differentiated between ischemic and hemorrhagic stroke in the proband. Family history of stroke was more frequent in large- and small-vessel stroke than in cardioembolic stroke. There were very few data on the influence of family history on stroke severity and no data on stroke recovery. CONCLUSIONS: Twin studies suggest a small genetic contribution to stroke, but reliable interpretation of published family history studies is undermined by major heterogeneity, insufficient detail, and potential publication and reporting bias. More detailed large-scale genetic epidemiology is required.